Monodisperse silica nanoparticle suspension for developing latent blood fingermarks - Liang Meng; Yifei Ren; Zhilong Zhou; Congxiang Li; Chen Wang; Shanlin Fu (Forensic Sciences Research, 2020)
Traditional fingermark developing methods are unsuitable for developing and extracting latent blood fingermarks on dark surfaces at crime scene because of their ineffectiveness or tedious operation procedures. In the present work, an effective and simple method was developed to serve this purpose using a suspension of monodisperse silica nanoparticles (MSNs). A suspension of 0.1 g/mL of MSNs was prepared by dispersing MSNs ultrasonically into an ethanol solution containing 1.0% Tween 80 and then uniformly sprayed onto the latent blood fingermarks on black plastic bags. Approximately 20 s later, ethanol was sprayed to clean the superfluous developing liquid. After the ethanol had evaporated, the latent fingermarks became visible as a result of the photonic crystal effect produced by the MSNs that had adsorbed to the fingermark ridges. The developed fingermarks were then photographed using a digital camera under a white or monospectral light source, revealing fine ridges and clear fingermark details. This novel, simple and effective method uses the photonic crystal effect of MSNs to develop latent blood fingermarks without the need for surface functionalization and conjugation to dye or fluorescently label molecules. The method can detect latent blood fingermarks that have been retained on a black plastic bag surface for at least 30 d. Given the simplicity and effectiveness of the developed method, MSNs may be a useful alternative material for use in developing latent fingermarks. Further research on the topic is warranted.